Development of Digital Marketing at Dimsum Lunaire MSMEs in Salatiga City through Content Marketing and Utilization of Artificial Intelligence - Abuk, Helena Alodia Widiasmara; Prasetyo, Rr. Agatha Ninacandra Kusumadewi; Listy, Glesheila Ayu Agelta; Pratiwi, Anita; Nugroho, Yosia Bagas Ferdian; Putri, Christina Ari Pramono (Jurnal Pengabdian Masyarakat, 2025)
Purpose: This study aims to provide training and assistance to Dimsum Lunaire MSMEs in Salatiga City to enhance their digital marketing capabilities through content marketing and the utilization of Artificial Intelligence (AI). The focus is on AI-driven product photo design, content creation, and website development to increase the competitiveness and sales of Dimsum Lunaire. Method: The community service activities were carried out through hands-on training and mentoring provided directly to the MSME owners. These activities included practical sessions on social media optimization, website development, and AI applications for efficient content marketing. Practical Applications: This initiative is designed to equip Dimsum Lunaire MSMEs with the necessary skills and knowledge to utilize digital marketing tools effectively. By leveraging social media platforms and AI, the MSMEs are better positioned to adapt to the digital era, improve their marketing strategies, and expand their customer base. Conclusion: The community service has demonstrated that digital marketing training and support for Dimsum Lunaire MSMEs resulted in valuable outcomes such as well-structured content plans, high-quality product photos, engaging content designs, and an operational website. These resources will enable Dimsum Lunaire to continue developing and improving their digital marketing efforts.